Circular RNA PTK2 modifies the progression and radiosensitivity in gastric cancer via miR-369-3p/ZEB1 axis. Issue 3 (9th January 2020) - Liu, Yuqiang; Yao, Kun; Zhang, Ke; Wang, Jianping; Dai, Qiang; Wang, Rong
Abstract : Circular RNA PTK2 regulates the cell proliferation, apoptosis, mobility and radiosensitivity via ZEB1 by sponging miR-369-3p in gastric cancer. Abstract : Gastric cancer (GC) is one of the common cancers worldwide. Emerging findings imply that aberrant expression of circular RNA_0003221 (circPTK2) is involved in GC. Nevertheless, the function of circPTK2 in GC needs more explanation. Profiles of circPTK2, microRNA (miR)-369-3p, and zinc finger E-box binding homeobox 1 (ZEB1) were determined by quantitative real-time polymerase chain reaction assay. 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide, flow cytometry, and transwell assays were employed to estimate cell proliferation, apoptosis, and mobility in GC cells, respectively. Meanwhile, levels of ZEB1 and other indicated proteins were tested using western blot. Survival fraction was assessed utilizing clonogenic assay. Additionally, the role of circPTK2 in tumorigenesis was investigated via a xenograft tumor model. Dual-luciferase reporter, RNA immunoprecipitation, and RNA pull-down assays were conducted to confirm the interrelation between miR-369-3p and circPTK2 or ZEB1. Levels of circPTK2 and ZEB1 were markedly augmented, but miR-369-3p was downregulated in GC tissues and cells. CircPTK2 depletion restrained cell growth, metastasis, and epithelial–mesenchymal transition, and promoted radiosensitivity in GC cells. And circPTK2 depletion reduced tumor growth and metastasis in vivo . Moreover, the effect of circPTK2 silencing on cellular phenotypes and radiosensitivity was regained by miR-369-3p inhibitor. Furthermore, upregulation of ZEB1 could overturn miR-369-3p mimic-induced effect on cell metastasis and radiosensitivity of GC cells. Mechanically, circPTK2 was a sponge of miR-369-3p to separate ZEB1. CircPTK2/miR-369-3p/ZEB1 axis modulated cell behaviors and radiosensitivity in GC; thus circPTK2 might serve as a promising target for GC therapy.